Volcanic eruption eye-witnessed and recorded by prehistoric humans - Ulusoy, Inan; Sarikaya, M. Akif; Schmitt, Axel Karl (Quaternary science reviews, 2019)
Human footprints in hydrovolcanic ash near Çakallar volcano (Kula, Western Turkey) were discovered in 1968. A nearby pictograph interpreted as depicting Çakallar volcano would define it as the oldest site where humans demonstrably eye-witnessed a volca̶nic eruption and possibly artistically recorded it. Despite Çakallar's volcanological and cultural importance, its eruption age has remained controversial. Here, two independent dating methods, cosmogenic 36Cl and combined U-Pb and (U-Th)/He zircon (ZDD) geochronology, yielded the first internally consistent eruption ages controlled by detailed volcanostratigraphic mapping. Concordant 36Cl ages of 4.7±0.6 ka (errors 1σ) were obtained for a cone-breaching lava flow. ZDD ages for crustal xenoliths from scoria deposits directly overlying the footprints yielded an age of 4.7±0.7 ka. This firmly places the Çakallar eruption and prehistoric human footprints, and plausibly the rock art, into the Bronze Age, reinforcing the notion that prehistoric artwork recorded natural events.
Gesehen am 21.08.2019